Strategi Pengembangan Perguruan Tinggi Islam Di Era Society 5.0 - Abdullah, Abdullah; Suprayogo, Imam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Islamic higher education in Indonesia is very fast. However, this fame must be balanced not only in quantity, but in quality. The aim of the research is to find out the strategy for developing Islamic higher education in the 5.0 era. This study uses a methodological literature review with a descriptive approach to find sources and explore this research. The results of this investigation show that: 1) Improving the quality of education must go beyond institutional standards. 2) Interesting educational innovations. 3) Good organizational management by leaders.